The Predictive Value of Early-Life Trauma, Psychopathy, and the Testosterone–Cortisol Ratio for Impulsive Aggression Problems in Veterans. (August 2019) - Korpel, Pauline O. J.; Varkevisser, Tim; Hoppenbrouwers, Sylco S.; Van Honk, Jack; Geuze, Elbert
Background: In this study, we examined whether early-life trauma, psychopathy, and the testosterone/cortisol ratio predicted impulsive aggression problems in veterans. Method: A sample of 49 male veterans with impulsive aggression problems and 51 nonaggressive veterans were included in the study. Logistic regression analysis was performed with early-life trauma, primary and secondary psychopathy, and testosterone/cortisol ratio as continuous predictor variables; impulsive aggression status was entered as a binary outcome measure. Correlation analyses were conducted to examine pairwise relations among the predictors. Results: Results indicated that early-life trauma and secondary psychopathy, but not the testosterone/cortisol ratio or primary psychopathy, were significant predictors of impulsive aggression status. Conclusions: The current results indicate that early-life trauma and secondary psychopathy are risk factors for impulsive aggression problems among veterans. Future studies are needed to determine the exact causal relations among the variables examined here.